The Effect of Endoscopy on Patients with Malignant Esophageal Cancer after Medical Treatment and Chemotherapy - Liu, Yu; Zhao, Lingqiong; Tan, Xingping; Liu, Nana; Long, Teng (Computational and mathematical methods in medicine, 2022)
The esophagus is one of the most commonly used parts in a person’s life, and its importance is self-evident. With the unhealthy food diet, people are more and more likely to suffer from esophageal cancer, and there is an urgent need for breakthroughs in the treatment of esophageal cancer. This article is aimed at studying the effects of medical treatment and chemotherapy for patients with malignant esophageal cancer. To this end, this article proposes a treatment method based on endoscopy and improves the image imaging of the endoscopy and the image quality of the image and the edge processing of the image. At the same time, this article designs an experiment to conduct statistical analysis of the situation during the treatment process. The experimental results in this article show that the improved treatment method has a 21% increase in success rate compared with the existing treatment method. And the optimized image quality has increased by 27%. It can very well help the attending doctor to improve the efficiency of treatment in the actual treatment process. Its most important contribution is that through the edge optimization and image enhancement processing technology, the success rate of endoscopic treatment has been better improved, and the treatment efficiency has also been improved.